Determinants of Twelfth-Grade Students’ Intentions to Choose Distance Learning - Hendrian Hendrian; Cynthia Ayu Manggarani (Journal La Edusci, 2025)
This study examines the determinants of twelfth-grade students’ intention to choose Universitas Terbuka (UT), with particular emphasis on perceived digital learning flexibility, perceived academic reputation, perceived employability, and brand trust. Using an explanatory quantitative approach with a cross-sectional survey design, the study collected empirical data from 428 twelfth-grade senior high school students from public and private schools. Data were analyzed using Partial Least Squares Structural Equation Modeling with SmartPLS 4. The findings demonstrate that brand trust is the strongest predictor of choosing intention, followed by perceived digital learning flexibility, perceived employability, and perceived academic reputation. The model shows substantial explanatory power, explaining 61.2% of the variance in brand trust and 68.4% of the variance in enrolment intention. Mediation analysis further reveals that brand trust partially mediates the effects of flexibility, reputation, and employability on enrolment intention, indicating that favorable perceptions become more influential when translated into institutional trust. Findings suggest that UT’s competitiveness depends not only on functional advantages such as flexibility and affordability, but also on its ability to build strong institutional trust among prospective students.